Assessment of Projects Financed from Structural Funds in the Sustainable Development Perspective - Zofia GRÓDEK-SZOSTAK; Jadwiga ADAMCZYK (Communications of International Proceedings, 2021)
The aim of the article is to evaluate projects financed from Structural Funds from the requirement perspective of sustainable development. To achieve this goal, the desk research method was applied, followed by own research using a triangulation method of research techniques: computer-assisted questionnaire (CAPI), individual in-depth interview (IDI) and participant observation. Own research has shown that applying the principles of sustainable development in practice can be effective, regardless of the formal and substantive criteria required when applying for European funding. At the same time, regardless of the profile and type of activity, each of the surveyed entities pointed to the benefits of implementing the sustainable development policy.
Keywords: Sustainable Development; Structural Funds; Projects; Efficiency.